Contemporary Vision of Poverty and Islamic Strategy for Poverty Alleviation - Muhammad Syukri Salleh (SAGE Open, 2017)
Currently, irrespective of one’s religious, ideological, and political inclination, poverty is seen as a destructive force in all aspects. Subsequently, various strategies have been formulated to alleviate poverty. But what are actually the components of the destructive force of poverty in the vision of contemporary Muslim scholars? What kind of Islamic strategies have they formulated out of this vision? This article seeks to answer these two main questions by first investigating into the contemporary vision of poverty that has been adopted by Muslim scholars, followed second by an investigation into the strategies for poverty alleviation they proposed, and third, by critically analyzing their vision of poverty and strategies from an Islamic perspective. Based on a textual analysis of references, this article displays an inadequacy of the vision and strategies of the contemporary Muslim scholars for ignoring material-spiritual definition of poverty, as well as for formulating strategies for poverty alleviation using an exogenous, top-down approach. In a nutshell, this article attempts to provide a justification for rescrutinization of the vision of poverty from an Islamic perspective, and for a reconstruction of the poverty alleviation strategies based on the faith of the Muslim communities themselves.